2019
DOI: 10.1093/nar/gkz766
|View full text |Cite
|
Sign up to set email alerts
|

HIF-transcribed p53 chaperones HIF-1α

Abstract: Chronic hypoxia is associated with a variety of physiological conditions such as rheumatoid arthritis, ischemia/reperfusion injury, stroke, diabetic vasculopathy, epilepsy and cancer. At the molecular level, hypoxia manifests its effects via activation of HIF-dependent transcription. On the other hand, an important transcription factor p53, which controls a myriad of biological functions, is rendered transcriptionally inactive under hypoxic conditions. p53 and HIF-1α are known to share a mysterious relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 119 publications
(159 reference statements)
2
27
0
Order By: Relevance
“…S3D). FRET on beads assay results is in agreement with the recent finding that p53 interacts with HIF-1 complex upon chromatin for adaptive responses in hypoxia (30). Next, the complex was checked against anti-p53, anti-HIF-1α, and anti-HIF-1β antibodies by two different modes in order to identify homo-oligomeric state of p53 that associates with the HIF-1.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S3D). FRET on beads assay results is in agreement with the recent finding that p53 interacts with HIF-1 complex upon chromatin for adaptive responses in hypoxia (30). Next, the complex was checked against anti-p53, anti-HIF-1α, and anti-HIF-1β antibodies by two different modes in order to identify homo-oligomeric state of p53 that associates with the HIF-1.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, D⇀T can promote T-HIF-1 complex which displays a chaperone function of p53. Recently, it has been shown that WT and MT p53 binds to HIF-1 complex at chromatin for its stabilization upon HRE in controlling angiogenesis and other HIF-1α induced transformations in hypoxic tumor progression (30). Our three chromophore FRET setup identifies a distal and proximal arrangement of two HIF-1 subunits, α and β in hypoxia and normoxia by the presence of p53 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of the tumor metabolism modeling approach, it has been shown that in the hypoxic microenvironment, both intracellular and environmental factors contribute to metabolic reprogramming of cancer cells, and that various growth factor-initiated cell signaling cascades and transcription factors can affect HIF-1 activity [39]. An interplay between HIF-1 and a variety of oncogenes such as Ras, c-Myc, p53, AMPK, along with PKB/Akt, PI3K, and mTOR signaling pathways has been observed to control mitochondrial ETC functioning and energy production to maintain cancer cell proliferation and survival [40][41][42][43][44][45][46][47].…”
Section: Hypoxia-inducible Factorsmentioning
confidence: 99%
“…HIF is a heterodimeric complex, consisting of α subunits (HIF-1α, HIF-2α, or HIF-3α) and a β subunit (also known as aryl hydrocarbon receptor nuclear translocator or ARNT). Expression of the α subunit is regulated by oxygen concentration in the cytoplasm, while the β subunit is constitutively expressed in the cell nucleus (7,8). Both α and β subunits, which contain a basic helix-loop-helix (bHLH) domain and a PAS-A and PAS-B (Per, Arnt, and Sim; PAS) domain, could combine as a heterodimeric complex to bind to the hypoxia response element (HRE) within specific sequences of the promotors of target genes.…”
Section: Structure and Activation Of Hypoxia-inducible Factors (Hifs)mentioning
confidence: 99%